PERSONALITY PHENOMENON: FACTORS INFLUENCING PERSONALITY DEVELOPMENT - Dinar Kerimova (Research Retrieval and Academic Letters, 2025)
The article examines the phenomenon of personality as one of the main research objects of social and humanitarian sciences and explains the leading role of upbringing in its formation on scientific grounds. It is emphasized that personality is a complex system resulting from the interaction of biological, psychological and social factors. It is noted that the upbringing process is a strategic tool that forms the value system of the personality, behavioral models, skills for entering social relations and moral qualities. The article comparatively analyzes the functions of social institutions such as family, school, society and mass communication in the development of personality. The stages of personality development - early childhood, school period and adolescence - are described, and the essence of the upbringing effect at each stage is explained. The analyses show that in conditions of effective upbringing, the creative potential, social adaptation skills and emotional-intellectual development of the individual are formed more dynamically. As a result, the article substantiates the importance of modern upbringing concepts as the main mechanisms affecting the harmonious development of the personality and puts forward scientific and practical recommendations for improving the upbringing system.